Cálculo do preço de venda como fator de competitividade para produtos fabricados por micro e pequenas indústrias - Bernardi, Arlos Renato (2005)
This thesis, entitled 'Calculation of retail price as an important factor of competitive advantage for manufactured products by small business', will present a mathematical model for product price calculation in small business. These model are founded in the Accountant Theory and in the way that prices are calculated by these industries. These retail prices, calculated by this model, must be seen by the companies as the smallest possible prices able to lead them to their planned targets, since the products made by them are manufactures and sold according to a deadline and quantity previously considered at the moment of prices arrangements, and not further investments will be needed. Therefore, these prices are classified as competitive for some products, regarding the real competition.